1996
DOI: 10.1093/infdis/173.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response Patterns against Schistosoma mansoni in a Recently Exposed Community in Senegal

Abstract: Acquired immune resistance is believed to be largely responsible for age-dependent infection and reinfection patterns in schistosomiasis. In a recently established but intense focus of Schistosoma mansoni in Senegal, the humoral immune response was studied in a random population sample of 289. Antibody levels of various isotypes to schistosome worm and egg antigens were determined by ELISA and related to egg counts (eggs per gram of feces [EPG]), age, and sex. Both IgG1 and IgG4 followed age-related patterns s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
41
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 45 publications
12
41
0
Order By: Relevance
“…2), and they were strongly associated with those previously measured to SEA and CERC (Table 1). Similarly to previously published age profiles of IgG1 and IgG2 responses to SEA (16,21,28), levels of IgG1 against LDN-DF decreased with age ( Fig. 1).…”
Section: Discussionsupporting
confidence: 89%
“…2), and they were strongly associated with those previously measured to SEA and CERC (Table 1). Similarly to previously published age profiles of IgG1 and IgG2 responses to SEA (16,21,28), levels of IgG1 against LDN-DF decreased with age ( Fig. 1).…”
Section: Discussionsupporting
confidence: 89%
“…8 Most isotypes showed an increase in absolute levels following praziquantel treatment, since release of antigens boosts the immune system. We found no consistent linear trend in antibody levels between the 4 cohorts, indicating an immunologically stable situation, in parallel with the parasitologic data.…”
Section: Discussionmentioning
confidence: 99%
“…Specific antibody levels (IgG, IgG1, IgG3, IgG4, IgM, and IgE) against adult worm antigen (AWA) were determined in serum as previously described in detail. 8 For the IgG1 assay, serum samples were diluted 1/ 2,000. Specific IgG2 and IgA were not measured because the previous study showed levels of these antibodies to be very low in this community.…”
Section: Population Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 IgG 4 has been detected in other parasitic infections, and selectively detecting IgG 4 can improve specificity. [14][15][16][17] This is supported in our study, where the IgG 4 were treated with SDS and heated at 65°C for 15 minutes, separated, and analyzed using SDS gel electrophoresis and Western blotting. Gels were transferred to nitrocellulose membranes and probed with a pooled positive F. hepatica human sera (fascioliasis+), a pooled negative human sera (negative human sera), and a pooled strong enzyme-linked immunosorbent assay-positive Toxocara human sera (toxocariasis+), all of which were diluted 1:100 in phosphate-buffered saline (PBS) + 0.3% tween + 5% milk.…”
mentioning
confidence: 77%